Sustainability performance of space-cooling technologies and approaches - Omer Abedrabboh (17346847) (2022)
Global warming causes an increase in the average ambient temperatures worldwide, resulting in a further increase in the cooling load demand of indoor spaces such as buildings and agricultural greenhouses; both are critically important for humans and other living creatures. While fulfilling the cooling needs of such, there has also been a crucial constraint to reducing the energy consumption and carbon emissions associated with cooling systems. Alternative cooling approaches are being developed in hopes of replacing conventional refrigeration systems. This study first presents findings of a comprehensive comparative literature review and analysis of various active cooling cycles in three main categories: Vapor-compression cycles (vapor-compression with different hydrofluorocarbon, hydrochlorofluorocarbon, and eco-friendly refrigerants), thermally-driven cycles (absorption, adsorption, and ejector), and emerging cycles (elastocaloric, electrocaloric, magnetocaloric, thermoacoustic, thermoelectric, and thermotunneling). Then, it presents investigations on the development of a sustainability performance index to comprehensively compare different cooling approaches. The sustainability performance is derived from several parameters obtained from the environmental, economic, and energy impact of cooling. Vapor-compression cycles joined with two emerging technologies (i.e. electrocaloric and magnetocaloric) achieved high sustainability scores, where vapor-compression-R510A obtained the highest sustainability score of 76.77%, followed by electrocaloric and vapor-compression-RE170, scoring 75% and 73.3%, respectively. Other Information Published in: Energy Sources, Part A: Recovery, Utilization, and Environmental Effects License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/15567036.2022.2127979